Optimization of Cultural Conditions for Keratinase Production by Curvularia lunata (JK17) using Response Surface Methodology - Meenakshi; Kumar, J.; Yadav, R. (Journal of Scientific Research, 2022)
This study presents optimum cultural conditions for the maximum keratinase production in SSF applying response surface methodology. The maximum enzyme activity of 123 U/mL for Curvularia lunata was observed at cultural condition 12.72 days incubation, temp. 35oC, 5.6 g feather, 4.9 g carbon, 5.9 g nitrogen. Three-dimensional response surface and contour plots were drawn to find the relationship between keratinase production and cultural conditions. These values optimum for keratinase production by Curvularia lunata were in good accord with the experimental result.